2008
DOI: 10.1523/jneurosci.2744-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Synaptogenesis in the Hippocampus Is Dependent on UCP2-Regulated Mitochondrial Adaptation

Abstract: Mitochondria are essential organelles in neurons providing appropriate energetic needs to maintain resting and action potentials as well as to modulate synaptic plasticity. Although neuronal events underlie various behavioral events, the behavior itself, such as voluntary exercise, feeds back to affect neuronal morphology and function as well as glial morphology and function. The hippocampal formation is a main site of synaptic plasticity induced by voluntary exercise. Here we show that voluntary exercise indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 29 publications
6
82
0
3
Order By: Relevance
“…ER and mitochondria have been reported to participate in dendritic spine formation (35)(36)(37)(38)(39). Our results provide additional insights on how these two intracellular organelles may participate in dendritic spine formation in a unique fashion.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…ER and mitochondria have been reported to participate in dendritic spine formation (35)(36)(37)(38)(39). Our results provide additional insights on how these two intracellular organelles may participate in dendritic spine formation in a unique fashion.…”
Section: Discussionsupporting
confidence: 51%
“…Contrary to the notion that ER does so by regulating Ca 2ϩ efflux via ryanodine or IP 3 receptors on the ER membrane (35-37), our results indicate that the ER might regulate dendritic spine formation in hippocampal neurons via a free radical-related mechanism that might not involve Ca 2ϩ signaling. Mitochondria supply energy for cells and are important in neural development (38,39). Our results indicate that mitochondria might participate in dendritic formation via a TIAM1-Rac1⅐GTP signaling pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Another means of enhancing mitochondrial function is exercise. Physical activity is a potent stimulator of mitochondrial biogenesis in muscle, heart and brain, which leads to enhanced oxidative phosphorylation activity and a corresponding increase in oxygen consumption and ATP synthesis [57][58][59] . Although the modulating effects of ex ercise on retinal mitochondria are yet to be shown, preliminary evidence suggests that vigorous physical activity may reduce glaucoma risk [60] .…”
Section: Methods Of Protecting Retinal Ganglion Cells From Injurymentioning
confidence: 99%
“…The results showed that combination therapy group with G-CSF and simvastatin was superior to either one alone in increasing synaptic vesicles density in the boundary zone around the hematoma. It appears that synaptic vesicles play critical role in regulating synaptic reorganization (6). Besides, the combined treatment group had significant neurological improvement from 1 week post-ICH onward.…”
Section: Acknowledgmentsmentioning
confidence: 87%